Hexafluoroisopropanol-Promoted Substitution Toward the Synthesis of Enantiopure Ferrocene Phosphines - Boussandel, Sirine; Erb, William; Roisnel, Thierry; Blot, Marielle; Hurvois, Jean-Pierre; Butler, Ian; Samarat, Ali; Mongin, Florence (Synthesis, 2025)
Enantiopure ferrocene-based phosphorus derivatives represent an important class of compounds with multiple applications in organic synthesis and coordination chemistry. Here, we report how the use of hexafluoroisopropanol can favor pseudo-benzylic substitutions toward both bulky diphosphine ligands and phosphonate derivatives. While the former can be involved in the formation of metal complexes, the latter can be easily reduced to original enantiopure ferrocenic primary mono- and diphosphines.
Keywords: Ferrocene; Primary phosphine; Chirality; Hexafluoroisopropanol; Substitution; Complexes